Effect of Structural Condition of Milk Processing Facilities and Food Safety Systems on Escherichia coli and Coliforms Presence in Cultured Buttermilk - Annah S. Paraffin; Titus J. Zindove; Michael Chimonyo (Journal of Food Quality)
The study investigated the effect of structural conditions of milk processing facilities and food safety systems on E. coli and coliform presence in buttermilk. Milk records collected by Dairy Services Zimbabwe (DSZ) from large-scale dairy milk processors (n=12) and small-scale farms (n=15) were analysed. Binomial logistic regression was used to estimate the likelihood of E. coli or coliforms being present in cultured buttermilk as a function of the hygiene level and structural adequacy of the processors. The likelihood of having E. coli and coliforms in cultured milk from processors with poor sanitary premises was two times higher than that from processors with good sanitary premises (P<0.05). Milk processors that used unfiltered water were 1.77 times more likely to produce cultured buttermilk contaminated with E. coli (P<0.05). Processors without food safety systems like hazard analysis critical control point (HACCP) systems were more than twice likely to produce cultured buttermilk contaminated by E. coli and coliforms (P<0.05). Poor structural condition of roofs, windows, insect-proof screens, and drainage in small- and large-scale processing facilities results in production of cultured buttermilk that is contaminated by E. coli and coliforms.